Carbon source, cell density, and the microbial community control inhibition of V. cholerae surface colonization by environmental nitrate - Jamaurie James; Renato E.R.S. Santos; Paula I. Watnick (mBio)
ABSTRACT The intestinal diarrheal pathogen Vibrio cholerae colonizes the host terminal ileum, a microaerophilic, glucose-poor, nitrate-rich environment. In this environment, V. cholerae respires nitrate and increases transport and utilization of alternative carbon sources via the cAMP receptor protein (CRP), a transcription factor that is active during glucose scarcity. Here, we show that V. cholerae nitrate respiration in aerated cultures is under control of CRP and, therefore, glucose availability. V. cholerae nitrate respiration results in extracellular accumulation of nitrite because V. cholerae does not possess the machinery for nitrite reduction. This nitrite inhibits V. cholerae biofilm formation via an as-yet unelucidated mechanism that depends on the high cell density master regulator HapR. The genome of Paracoccus aminovorans, an intestinal microbe identified in the microbiome of cholera patients that has been shown to enhance V. cholerae biofilm accumulation in the neonatal mouse gut, encodes enzymes that reduce nitrite to nitrogen gas. We report that, in nitrate-supplemented co-cultures, P. aminovorans metabolizes the nitrite generated by V. cholerae and, thereby, enhances V. cholerae surface accumulation. We propose that V. cholerae biofilm formation in the host intestine is limited by nitrite production but can be rescued by intestinal microbes such as P. aminovorans that have the capacity to metabolize nitrite. Such microbes increase V. cholerae colonization of the host ileum and predispose to symptomatic infection.IMPORTANCEVibrio cholerae colonizes the terminal ileum where both oxygen and nitrate are available as terminal electron acceptors. V. cholerae biofilm formation is inhibited by nitrate due to its conversion to nitrite during V. cholerae respiration. When co-cultured with a microbe that can further reduce nitrite, V. cholerae surface accumulation in the presence of nitrate is rescued. The contribution of biofilm formation to ileal colonization depends on the composition of the microbiota. We propose that the intestinal microbiota predisposes mammalian hosts to cholera by consuming the nitrite generated by V. cholerae in the terminal ileum. Differences in the intestinal abundance of nitrite-reducing microbes may partially explain the differential susceptibility of humans to cholera and the resistance of non-human mammalian models to intestinal colonization with V. cholerae.